Changes in the weight of calved cows in native pastures in the Pantanal. - OLIVEIRA, L. O. F. de (2015)
The weight variation of calving cows was followed during the spring in native pastures in the Pantanal. Each lot contained 100 multiparous and 40 primiparous cows submitted to protein (PS) or energy (ES) supplementation. The cows were put in an area of 596 hectares, divided into two paddocks with native pastures of medium and low nutritional value. A completely random manner design was applied. The covariates used for comparing the results were class (multiparous or primiparous) and postpartum days (pp) (> 60 or <60 days), with the Tukey test at 5% by the mixed linear model (procedure MIXED). The multiparous cows gained 26.55 and 36.10kg in the PS and ES supplementation periods, respectively. Primiparous PS cows lost -6.15kg and primiparous ES cows gained 4.19kg during the study period of 42 days. Multiparous and primiparous cows over 60 days pp and supplemented with energy (ES) had a greater weight gain (P <0.05) in their respective categories, thus demonstrating response to dietary improvements (pastures and supplements), possibly associated with the output of the postpartum negative energy balance, an effect more evident in the multiparous category. The native grassland with better nutritional value increased in frequency in relation to the lower value (23.45 to 37.66%) and improvement was observed in the chemical composition of forages (from 53.40 to 57.37% of total digestible nutrients).